(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
To humans, a chatbot is a fantastic advancement. A Chatbot’s use may be observed in a variety of sectors. The technique for planning and implementing a Chatbot is covered in this document. After learning the victim’s requirements, an Android-based bot may work with them. The main purpose of this system is to register an F.I.R through chatbot in an efficient manner. The main objective is to efficiently provide easy user interface to the victim(user) to gain information regarding different crimes as well as report crime through a fully automated chatbot system that not only saves lots of time but also gives realtime results. The system handles all the operations, including asking questions that is needed in order to report a crime and generates reports as soon as the victim(user) answers the questions, that includes name, email, and other personal questions. Simultaneously the police can access the generated report through a separate portal and can proceed to take action accordingly.